A organização criminosa na lei 12.850/13 - Lurizam Costa Viana (2017)
This work has as central scope the study of criminal organization in Brazilian criminal law, especially concerning the Law 12.850/13. Based on guiding principles of criminal guaranty, particularly the strict legality, the work seeks to investigate whether the criteria defining criminal organization in the law mentioned before are sufficient to differentiate it from other delinquent associative figures. Initially, in addition to highlighting the importance of the legal concept of criminal organization, the distinction between "mass criminality" and "organized criminality" was clarified. The main criminological aspects related to criminal organizations were identified, with emphasis on division of labor, relations with "golden crime", corruption, violence and use of technological resources to achieve criminal purposes. Having as support the comparative criminal law and international documents dealing with criminal organizations, especially the Palermo Convention, the Italian, Spanish and Portuguese models of criminal organization were analyzed, contributing later on to the study of the typical associative figure provided for in Law 12.850/13. In order to contextualize the legal treatment of organized crime in Brazil, Laws 9.034/95 and 12.694/12 were addressed, in addition to the guidelines followed in the Federal Supreme Court and the Superior Court of Justice in the scenario prior to Law 12.850/13. After that, the crime of criminal organization provided for in Law 12.850/13 was addressed, explaining the positions adopted in this research, particularly concerning the legal good protected and the consummation of the crime in question. From the analysis of the elements that define criminal organization according to Law 12.850/13, the initial hypothesis was confirmed, concluding that the use of vague expressions, to the detriment of the principle of strict legality, hinders the precise delimitation of the field of incidence of this crime, leading to difficulties especially when the criminal organization is compared with other criminal associative figures under Brazilian criminal law, including criminal association, paramilitary organization and private militia, association for the practice of genocide, association for traffic of illicit drugs and terrorist organization.